Genetic and non-genetic Factors affecting test day milk yield and milk composition traits in crossbred dairy cattle in Ethiopia - Bekele, R.; Taye, M.; Abebe, G.; Meseret, Selam (Chiang Mai University, 2023)
This study evaluated the effects of genotype, parity, days in milk (DIM), calving season (CS), and calving year (CY) on the milk yield and composition traits of four hundred twenty lactating crossbred dairy cows in 13 districts in Ethiopia. Test day milk yield (TMY), protein (P), fat (F), lactose (L), solid not fat (SNF), density (D), total solids (TS), total protein (TP), casein (CN), whey (W), salts (S), and freezing point (FP) were determined using standard procedures. The data were analyzed using generalized linear models (GLM) using R software. Cows in the genetic group ≥ 87.5%, at 101–200 days, calved in the rainy season, in 2022, and at second parity all had the highest value of TMY. F, SNF, and TS were significantly (P<0.05) influenced by genotype, DIM, CS, CY, and parity. F was higher in cows with ≤ 50% genetic group, in early and late lactation, in the dry season, in 2020, in primiparous and above parity three cows than their counterparts. Proteins (P, TP, CN, and W) were affected by genotype, DIM, and CY but not by CS and parity (P<0.05). All milk proteins had a higher value in cows with ≤ 50% genetic group, and in early lactation. In this study, milk yield and composition were affected by genetic and non-genetic factors, providing an opportunity for crossbreeding programs to balance the quality and quantity of milk by manipulating the level of the exotic gene found in cows, choosing the best agro-climatic conditions, and improving the level of management.